Floor finish selection in the design of healthcare facilities: a survey of facility managers. Issue 9 (15th February 2019) - Dixit, Manish K.; Singh, Shashank; Lavy, Sarel; Yan, Wei; Pariafsai, Fatemeh; Ostadalimakhmalbaf, Mohammadreza
Abstract : Purpose: The purpose of this study is to create a knowledge base for decision-making in healthcare design by seeking, analyzing and discussing the preferences of facility managers of healthcare facilities regarding floor finishes and their selection criteria. The goal is to enable a simplified and holistic selection of floor finishes based on multiple criteria. The authors studied floor finish selection in three healthcare units: emergency, surgery and in-patient units. Design/methodology/approach: The authors completed a literature review to identify types of floor finishes currently used in healthcare facilities and the criteria applied for their selection. Using the literature survey results, a questionnaire was designed and administered to healthcare facility managers. The descriptive statistical analysis and the Friedman and Wilcoxon signed-ranks tests were used for reporting and analyzing the survey data. Findings: The top five floor finishes used in the healthcare sector were identified as vinyl flooring, vinyl composite tile (VCT), rubber, linoleum and ceramic flooring. The top five selection criteria for floor finishes were durability, infection control, ease of maintenance, maintenance cost and user safety. The non-parametric test results show that the floor finish rankings and selection criteria were similar in the three healthcare units under study. Originality/value: The most significant contribution of this research is to the design decision-making process of healthcare facilities. These results offer an understanding of what floor finishes are preferred by healthcare facility managers and why. This knowledge is crucial for designers and facility managers to make informed choices and floor finish manufacturers to keep their product line relevant to the industry.